Protective role of the novel cytokine Metrnl/ interleukin-41 in host immunity defense during sepsis by promoting macrophage recruitment and modulating Treg/Th17 immune cell balance - Chen, Xi (Clinical immunology (Orlando, Fla.), 2023)
Copyright © 2023. Published by Elsevier Inc.